ELDERLY SCREENING IN SONGGON BANYUWANGI 2019 - Hakim, Lukman; Erlangga, Wildan Anugrah; Adi, Pandu Satriya; Septiana, Fitri Nurina; Arianti, Emilia Eka; Qualisa, Prafidina; Lamara, Ariikah Dyah; Meitavany, Estya Nadya; Fatimah, Niswah Silmi; A, Ulinnuha Qurrota; Sulistiawati, Sulistiawati (Universitas Airlangga, 2020)
Health care efforts for the elderly to keep the elderly healthy, independent, active and productive socially and economically , to realize this, the government is obliged to guarantee the availability of health service facilities and facilitate the development of the elderly group. The aims to identify factors that affect the achievement of health care coverage of the elderly. This was a qualitative descriptive study. This research was conducted in Songgon District . The target sample was the elderly residents and elderly Posyandu cadres. Data collection instruments using questionnaires. This study used primary data. Univariate analysis to determine the distribution using SPSS and Excel tools. 84% of elderly people knew about screening. The coverage of elderly screening was still low. From the results of research on community therapy that could be done was cadre training, reporting of the elderly, and Extension of Posyandu Elderly by Cadres for the Community